Prairie Fire: The Winnipeg General Strike - Korneski, Kurt (Labour / Le Travail, 2000)
Critiques the documentary, "Prairie Fire," including that the narrative is framed by the "western exceptionalist" historical interpretation, which narrows the Strike's significance.